Evaluation of Health Care Workers’ Knowledge about Integrated Management of Neonate and Child Health Program in Najaf Governorate/Iraq - Hussian Nadhim Rasoul; Hassan Ali Farman; Saad Saleem Raheem (مجلة الكوفة الطبية)
Background: Over 6 million children in the developing countries died due to avoidable illnesses, mostly pneumonia and diarrhea. The Integrated Management of Childhood Illness (IMCI) program was launched by the World Health Organization (WHO) in 1992. This program aims to provide a comprehensive approach to managing the primary causes of illness and death in children. Materials and Methods: A cross-sectional descriptive research study was carried out in 26 healthcare centers located in 6 districts of Najaf governorate, using the method of simple random sampling. The research study included a group of 111 healthcare workers. A questionnaire was used to evaluate the IMNCH skills of healthcare workers. The data collection got started on December 31, 2023, and finished on March 31, 2024. Results: The study findings indicated a significant level of high knowledge among healthcare workers. Additionally, a statistically significant link was observed between the healthcare workers' place of residence and their knowledge (P=0.05), suggesting that individuals living in urban regions have higher levels of knowledge compared to those residing in rural areas. Conclusion: Healthcare workers showed a high level of knowledge regarding IMNCH information, and the knowledge was strongly related to the healthcare worker's residences place and years of experience.